derivative of cosecant
To find the derivative of the cosecant function, we can use the quotient rule
To find the derivative of the cosecant function, we can use the quotient rule. The derivative of cosecant (csc) of x, denoted as csc(x), can be determined as follows:
Let us assume that y = csc(x), where x is the independent variable and y is the dependent variable.
Step 1: Express csc(x) in terms of sine (sin(x)):
csc(x) = 1/sin(x)
Step 2: Apply the quotient rule, which states that if y = u/v, where u and v are functions of x, then the derivative dy/dx is given by:
dy/dx = (v * du/dx – u * dv/dx) / v^2
In our case, let u = 1 and v = sin(x).
Step 3: Calculate the derivatives of u and v:
du/dx = 0 (since the derivative of a constant is always zero)
dv/dx = cos(x) (derivative of sin(x))
Step 4: Substituting the values into the quotient rule formula:
dy/dx = (sin(x)*0 – 1*cos(x)) / sin^2(x)
dy/dx = -cos(x) / sin^2(x)
Step 5: Simplify the expression:
dy/dx = -cos(x) / (1 – cos^2(x))
dy/dx = -1 / (sin(x) * (1/sin^2(x)))
dy/dx = -1 / (sin(x) / sin^2(x))
dy/dx = -1 / (1 / sin(x))
dy/dx = -sin(x)
Thus, the derivative of cosecant (csc(x)) is equal to -sin(x).
More Answers:
Understanding the Quotient Rule in Calculus | Differentiating Complex Functions Involving RatiosUnderstanding the Constant Factor Rule | A Fundamental Property of Multiplication in Mathematics
Understanding the Derivative of the Cosine Function | Chain Rule and Graph Interpretation